Criminal Law Analysis of Brawls Between Groups of Children: A Review from the Perspective of Psychological Criminology - Setyarini, Astri Dewi; Mulyadi, Mulyadi (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Brawl is a form of juvenile delinquency committed by children, in criminology, which explains the science of crime that continues to develop. Brawl can be studied from a psychological perspective. Prevention and serious handling of the legal vacuum are needed. The formulation of the problem that the examines is to find out brawls committed by children in the legal system in Indonesia, and to find out the causes of children's involvement in brawling through psychological criminology reviews. The purpose of this research is to find out the legal system in Indonesia regarding brawls committed by groups of children and how brawls are studied from the perspective of psychological criminology. This research uses a juridical-normative research method that emphasizes a qualitative approach by collecting and studying literature reviews through literature study research. The results of this study indicate that there is still a legal vacuum regarding brawls in Indonesia, both in general and specific laws, but the Juvenile Criminal Justice System still prioritizes Restorative Justice. Brawling itself can also be studied from the perspective of psychological criminology, where there are factors of children committing brawls, including internal factors, family factors, school factors, environmental factors, mental factors, and poverty factors. In addition to this, juvenile delinquency, such as brawls, also occurs because of the loss of Pancasila values.